Aplikasi Manajemen Kegiatan Ekstrakurikuler Berbasis Web di SMK Negeri 6 Padang - Telaumbanua, Nahwan Shaleh; Kurniadi, Denny (Lembaga Yasin AlSys, 2024)
Extracurricular activities, being non-academic pursuits conducted outside of regular school hours, are a common feature in many schools, including SMK Negeri 6 Padang. To streamline the registration and management of these activities, this application was developed. Employing a systematic waterfall methodology, the development process encompassed needs analysis, design, implementation, testing, and maintenance, culminating in a well-structured and reliable system. The application was built using PHP, MySQL, and UML, and its functionality and usability were assessed through black-box testing. This web application has been meticulously developed to facilitate the management of extracurricular data at SMK Negeri 6 Padang. Equipped with a comprehensive suite of features, the system enables users to effortlessly perform a wide range of administrative tasks.